The dilemma of diabetes in chronic inflammatory demyelinating polyneuropathy - Bril, Vera (J Diabetes Complications, 2016)
PURPOSE: We reviewed the literature on chronic inflammatory demyelinating polyneuropathy (CIDP) in diabetes mellitus (DM) and explored real-world data on the prevalence and treatment of CIDP within DM. Methods: A literature search of Scopus was performed for the terms chronic inflammatory demyelinating polyradiculoneuropathy, chronic inflammatory demyelinating polyneuropathy, CIDP, and prevalence, incidence, epidemiology, or diabetes; peripheral neuropathy and prevalence or diabetes. We also searched through the reference lists of the resulting publications for additional findings that may have been missed. Additional publications on guidelines for the diagnosis of CIDP and diabetic neuropathy were also included. A descriptive analysis of the 2009–2013 PharMetrics Plus™ Database was performed to estimate the prevalence and treatment of CIDP within the DM population. RESULTS: There is an increasing body of literature suggesting that the prevalence of CIDP tends to be higher in diabetic patients, especially in those of older age. Our real-world data seem to support published findings from the literature. For the total cohort (N = 101,321,694), the percent prevalence of CIDP (n = 8,173) was 0.008%; DM (n = 4,026,740) was 4%. The percent prevalence of CIDP without DM (n = 5,986) was 0.006%; CIDP with DM (n = 2,187) was 9-fold higher at 0.054%. For patients >50 years old, there was a significantly higher percentage of CIDP with DM than CIDP without DM. Approximately 50% of CIDP patients were treated with IVIg, 23%–24% with steroids, 1%–2% with PE, and 20%–23% received no treatment. CONCLUSIONS: In addition to the growing evidence of higher prevalence of CIDP in DM, our findings reinforce the need for heightened awareness of the association of CIDP and DM.